REVEALING A JAVANESE IDENTITY OF PRAYER IN THE WEDHATAMA THROUGH SEMANTIC PROPOSITION - Tantri Refa Indhiarti; Sri Utami Budi; Indah Winarni (Kajian Linguistik dan Sastra, 2017)
The  Wedhatama,  a  Javanese  literary  work  by  the  King  Mangkunegara IV  contains  philosophical  teachings  which  are  quite  influential  in  ethical life.  This  paper  aims  at discovering the hidden meaning of the teachings which reveal  an  esoteric  knowledge  of  worshipping  in  terms  of  its  semantic  point  of view.  This  meaning  is  known  through  analytic  and  synthetic  propositions  in Gambuh canto associated with 4 different types of worship. Thus, the qualitative paradigm is used in which the data were obtained through library research. In this  study,  the  synthetic  proposition  shows the  breadth  of  the  poet’s  signifying esoteric intention  that  is about Javanese identity of  prayer. It  is  revealed  that the  four  types  of  worship  –sembah  raga,  cipta,  jiwa,  and  rasa  –are  said  to coincide with what are usually referred to in Muslim Sufism as syariat. Keywords: Gambuh canto, the Wedhatama, Javanese identity of prayer, semantic proposition